2015
DOI: 10.5194/bg-12-2695-2015
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dissolved and total organic matter in throughfall, stemflow and forest floor leachate of central European forests

Abstract: Abstract. We present the first investigation of the composition of dissolved organic matter (DOM) compared to total organic matter (TOM, consisting of DOM, < 0.45 µm and particulate organic matter 0.45 µm < POM < 500 µm) in throughfall, stemflow and forest floor leachate of common beech (Fagus sylvatica L.) and Norway spruce (Picea abies (L.) H. Karst.) forests using solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy. We hypothesized that the composition and properties of organic matter (OM) in for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…This agrees with findings of Lorenz et al (2004), who reported higher concentrations of tannins in beech leaf litter than in pine needles. A higher share of phenolic carbon in beech than spruce solution samples from the same plots than this study was also found by Bischoff et al (2015), based on 13 C NMR analysis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This agrees with findings of Lorenz et al (2004), who reported higher concentrations of tannins in beech leaf litter than in pine needles. A higher share of phenolic carbon in beech than spruce solution samples from the same plots than this study was also found by Bischoff et al (2015), based on 13 C NMR analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Dissolved organic matter (DOM) processing and transport is highly dynamic in forest ecosystems (Kaiser and Kalbitz, 2012) and plays an important role in the biogeochemical cycles of carbon and nutrients (Bolan et al, 2011;Kaiser and Kalbitz, 2012). The chemical composition of DOM strongly affects its role in the carbon and nutrient cycles of ecosystems (Bolan et al, 2011). The chemical composition, in turn, depends on the DOM source and its processing along the water flow path through ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How might this change with tree age and change in bark structure? NMR spectroscopy may prove useful to examine the chemical character of PM in stemflow [ Bischoff et al ., ]. The variety of plant surfaces is as vast as the number of tree species.…”
Section: Stemflow: Dissolved Organic and Particulate Matter Dynamicsmentioning
confidence: 99%
“…DOC pools are denoted from S1 to S7. Although SOC (including litter leachate) near the riparian areas constitutes the main carbon pool in headwater tropical catchments, organic matter from throughfall (1-61 mg/L) and stemflow (7-482 mg/L; often stored and released from mosses, ferns, lichens, and bromeliads) may also contribute a significant DOC pulse during large rain events (Bischoff et al, 2015;da Costa et al, 2017;Van Stan & Stubbins, 2018) to the overall fluvial carbon budget.…”
Section: Key Drivers Controlling Tropical Doc Transport and Exportmentioning
confidence: 99%